(untitled) - Baran, Stanley J.; Stanley J. Baran (Boston, 2009)
This text encourages students to take more active roles as media consumers and gives them a deeper understanding of the role that the media play in both shaping and reflecting culture. Through this cultural perspective, students learn that audience members are as much a part of the mass communication process as are the media producers, technologies, and industries. This was the first university-level text to make media literacy central to its approach
Includes bibliographical references and index
Keywords: Mass media; Mass media and culture; Mass media literacy